Corporate financial and investment policies when future financing is not frictionless - Almeida, Heitor; Campello, Murillo; Weisbach, Michael S. 1961- (NBER working paper series, 2006)
Much of corporate finance is concerned with the impact of financing constraints on firms. However, the literature on financing constraints largely ignores the intertemporal implications of those constraints; in particular, how future financing constraints affect current investment decisions. We present a model in which future financing constraints lead firms to have a current preference for investments with shorter payback periods, investments with less risk, and investments that utilize more liquid/pledgeable assets. The model has a host of implications in different areas of corporate finance, including firms' capital budgeting rules, risk-taking behavior, capital structure choices, hedging strategies, and cash management policies. We show how a number of patterns reported in the empirical literature can be reconciled and interpreted in light of the intertemporal optimization problem firms solve when they face costly external financing. For example, contrary to Jensen and Meckling (1976), we show that firms may reduce rather than increase risk when leverage increases exogenously. Furthermore, firms in economies with less developed financial markets will not only take different quantities of investment, but will also take different kinds of investment (safer, short-term projects that are potentially less profitable). We also point out to several predictions that have not been empirically examined. For example, our model predicts that investment safety and liquidity are complementary: constrained firms are specially likely to distort the risk profile of their most liquid investments.